The use of tandem yeast and mammalian cell in vitro androgen bioassays to detect androgens in internet‐sourced sport supplements. Issue 4 (27th June 2016) - Cooper, Elliot R.; McGrath, Kristine C.Y.; Li, Xiaohong; Akram, Omar; Kasz, Robert; Kazlauskas, Rymantas; McLeod, Malcolm D.; Handelsman, David J.; Heather, Alison K.
Abstract : Sport supplements containing steroids never approved for therapeutic use have the potential for abuse by athletes. Most are marketed online and may contain undisclosed steroids yet are readily available despite lacking toxicological or pharmacological evaluation. In this study, 18 supplements purchased online underwent organic solvent extraction to isolate any steroids they contained. From the 18 supplements, 19 steroids were identified and for each, its intrinsic androgenic potency was determined by a yeast cell ( Saccharomyces cerevisiae ) androgen bioassay and its potential androgenic potency was determined by a liver (HuH7) cell androgen bioassay. The yeast bioassay showed that of the 19 steroids tested, 6 demonstrated strong intrinsic bioactivity, with 4 metabolically activated to even stronger androgens. Moreover, 4 steroids with moderate and 1 with intrinsically weak androgenic bioactivity were activated to more potent androgens. Finally, 8 steroids were metabolically inactivated or deactivated into weaker androgens. Our results show that Internet‐sourced sport supplements may contain intrinsically strong androgens, or precursors that can be metabolized to them. These potentially potent pharmacologically active steroids are being used without regulatory control or consumer awareness of their potential adverse effects. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Sport supplements may contain steroids never approved for therapeutic use. In this study, 18 sport supplements purchased online underwent organic solvent extraction and subsequent isolated steroid tested for intrinsic androgen bioactivity. Many were found to be strong androgens. These potent pharmacologically active steroids are being used without regulatory control or consumer awareness of their potential adverse effect.